Respuesta :

Answer:

Step-by-step explanation:

P(x)= x^2-5x+c=0

P (-2)= (-2)^2-5 (-2)+c=0

= 4+10+c=0

=14+c=0

C=(-14)

Answer:

[tex]\fbox{\begin{minipage}{4em}c = -14\end{minipage}}[/tex]

Step-by-step explanation:

Given:

A quadratic equation: [tex]x^{2} - 5x + c = 0[/tex], with [tex]x =-2[/tex] is a solution.

Solve for:

Value of c

Step 1: define the problem

If [tex]x = -2[/tex] is a solution of equation [tex]f(x) = 0[/tex], then [tex]f(-2) = 0[/tex]

Step 2: Perform the calculation

Substitute [tex]x = -2[/tex] into original quadratic equation, we have:

[tex](-2)^{2} - 5(-2) + c = 0[/tex]

Perform the square and multiplication:

[tex]4 + 10 + c = 0[/tex]

Transfer all of numbers to the right side, except c:

(notice for the change in sign of numbers)

[tex]c = (-4) + (-10)[/tex]

Perform the sum on the right side to get c:

[tex]c = -14[/tex]

Hope this helps!

:)